Aí! Tá me tirando?! O que dizem jovens moradores da periferia de São Carlos sobre si mesmo e a questão das drogas - Pereira, Paulo Estevão (2012)
The drugs phenomenon is becoming more relevant in Brazil and worldwide in recent decades, reaching all levels of society. The frequent association between groups of youngsters, especially poor youth, and drug use, present in the media and in the public policies, has raised discussions and interventions that need to be analyzed and problematized in their propositions and development. Such interventions have not considered the socioeconomic and cultural situation that these youngsters are submitted, accumulating ineffective results. This data raises the need to take a "step back" in argument, reversing the order of the question and inquire, a posteriori about the best way to treat these young people in use or abuse of drugs - an issue undoubtedly relevant - and start asking first which are the social contexts and the social arrangements that put these youngsters in a vulnerable situation to the drugs issue and how this exposure occurs in their daily practices. In order to investigate how drugs make up the path of poor youngsters who live in outlying areas was undertaken a qualitative research that aimed to access the experiences of young people, between 15 and 29 years old, living on the outskirts of a medium-sized city in the State of São Paulo, which attending to a social institution dedicated to leisure, culture and sports activities. The methods applied to reach the aims were the participant observation, semi-structured interviews and workshops of Activities. The propositions of social occupational therapy constituted the theoretical background of the study. The use of participatory methodologies in the apprehension of the universe of subjects studied allowed accessing their perceptions about the drug issue, pointing out, however, other issues that permeate their daily experiences, determining their condition of vulnerability. Issues such as the constant violations of their civil rights; restrictions to urban mobility; social stigma; real and/or symbolic violence; the centrality of work and their links with and through the drug trafficking, emerged from the reports of these young people, enabling to build a picture of the extended social context in which they are located, indicating that, although present in everyday life, drugs are not the main source of concern or of increasing of the vulnerability of these young people.